Penerapan Pendekatan Realistic Mathematics Education (RME) untuk Meningkatkan Hasil Belajar Matematika pada Materi Penjumlahan dan Pengurangan Bilangan Cacah Siswa Kelas I MIN Solok Selatan - Mitraturrahmi, Mitraturrahmi (Journal of Development Education and Learning (JODEL), 2025)
Mathematics learning in the foundational phase plays a strategic role in developing students’ basic numeracy skills. However, conventional teaching approaches often cause difficulties, especially in addition and subtraction with whole numbers. This study was conducted in Grade I MIN I Solok Selatan with 17 students, where diagnostic assessment revealed that only 31% achieved the intended learning outcomes (KKTP). The average score was 65, below the minimum mastery criterion. This study aims to describe how the implementation of Realistic Mathematics Education (RME) can improve learning outcomes and student activity. The research employed Classroom Action Research (CAR) using the Kemmis and McTaggart model across two cycles. Data were collected through observations, achievement tests, and documentation, and analyzed quantitatively and qualitatively. Findings indicated significant improvement: the average score increased from 65 (31.25% mastery) to 72.5 (68.75%) in cycle I, and 84.38 (93.75%) in cycle II. Student engagement also improved, with 85% actively participating in discussions and modeling problems. These results support constructivist theory and demonstrate that RME is effective for mathematics learning at the foundational level.